Lingua spagnola in drammaturgia fiorentina. Il caso di Baltasar Suárez (1623-1666) - Vuelta García, Salomé (Drammaturgia, 2014)
The essay reports on Baltasar Suárez de la Concha (1623-1666) and on his role as a cultural-linguistic mediator in Florence in mid-XVIIth century as a member of one of the most powerful Spanish families of the Medici town. His translating activity for the stage comes to the surface thanks to the analysis of two unpublished manuscripts: the grammar notes and the dictionary Spanish-Italian, both connected to the comedy Ofender con las finezas by Jerónimo de Villaizán (1636), and the play Carlo perseguido, a translation he made of Carlos el perseguido by Lope de Vega (1604). Il saggio tratta di Baltasar Suárez de la Concha (1623-1666) e del suo ruolo di mediatore linguistico-culturale nella Firenze di metà Seicento, in quanto membro di una delle più potenti famiglie spagnole della città medicea. La sua attività di traduttore teatrale emerge dall’analisi di due manoscritti inediti: gli appunti grammaticali e il vocabolario spagnolo-italiano relativi alla commedia Ofender con las finezas di Jerónimo de Villaizán (1636), e l’opera Carlo perseguido, sua traduzione di Carlos el perseguido di Lope de Vega (1604).